Humour in the Stories about Buster Oregon Mortensen - Takle, Cecilie (Nordlit, 2023)
This article examines humor in three different versions of the story about Buster Oregon Mortensen, from 1979, 1984 and 2021. I perform a comparative analysis as a thematic close reading of the three works with a particular interest in humor in relation to power balance and themes perceived as difficult or taboo.